Risk Management in Construction Projects 2019
DOI: 10.5772/intechopen.85607
|View full text |Cite
|
Sign up to set email alerts
|

Holistic View on Multi-Stakeholders’ Influence on Health and Safety Risk Management in Construction Projects in Tanzania

Abstract: Construction projects constitute complex and dynamic systems, which pose high health and safety risks to the practitioners. As a result, many researchers have underscored the importance of risk management that requires inputs from all stakeholders across different stages of the construction project from the design up to the construction phase. However, there is a limited knowledge about stakeholders' influence on health and safety risk management in building construction projects in Tanzania. To fill this gap,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This single common factor appeared in the nine opinion-based studies, ranked nine times in the top ten, six of which were in first place. This coincides with findings by [10] and Phoya et al [11], where falls from heights in Malaysia and Tanzania were found to be the most significant cause of accidents in their construction industries.…”
Section: Discussionsupporting
confidence: 92%
“…This single common factor appeared in the nine opinion-based studies, ranked nine times in the top ten, six of which were in first place. This coincides with findings by [10] and Phoya et al [11], where falls from heights in Malaysia and Tanzania were found to be the most significant cause of accidents in their construction industries.…”
Section: Discussionsupporting
confidence: 92%
“…Stakeholders have a varied spectrum of influence in accordance with their interests and attitudes [49]. Our findings showed that the MOHME and the parliament have highest influence on PRF-related polices.…”
Section: Discussionmentioning
confidence: 72%
“…FMEA adalah suatu metode yang umum digunakan oleh engineers untuk mengidentifikasi mode kegagalan, penyebab kegagalan dan efek dari kegagalan secara sistematik (Hyatt, 2003). Keunggulan metode FMEA sebagai analisis risiko dibandingkan dengan metode lain adalah metode lain hanya mempertimbangkan variable seperti severity dan occurrence, sedangkan FMEA memiliki variable detection atau variable yang menilai kemampuan perusahaan dalam mengelola risiko sehingga dapat mendeteksi kegagalan (Phoya, 2012) .…”
Section: Gambar 1 Diagram Keterkaitan Masalahunclassified